Dragonfly (Odonata) Species Diversity in the Sigolo-Golo Tourism Area, Jombang, East Java - Zumar, Muhammad Rifqi; Romzalis, Ahmad Alfin; Wibisana, Oki Rahmatirta; Susanto, Muhamad Azmi Dwi (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2023)
The sigolo-golo area is a tourist area with waterfalls and rivers. It is located in a secondary forest far enough from settlements, so it has the potential to be a habitat for dragonfly diversity. This study aims to analyze the composition and diversity of dragonflies in the Sigolo-golo tourist area. Data collection was carried out using the Visual Encounter Survey (VES) method. The results of research conducted in three locations showed that there were 12 species from five families, namely Libellulidae, Euphaeidae, Calopterygidae, Chlorocyphidae, and Platicnemididae, with a total of 319 individuals. The species with the highest relative abundance value in this study was Pantala flavescens with a value of 77.40%. The value of species diversity at this location is H' = 0.984, which indicates that the diversity index value is low.ABSTRAK: Kawasan Sigolo-golo merupakan area wisata dengan terdapat air terjun dan sungai, yang terletak di dalam hutan sekunder yang cukup jauh dari pemukiman, sehingga berpotensi sebagai habitat bagi keanekaragaman capung. Penelitian ini bertujuan untuk menganalisis komposisi, dan keanekaragaman capung di kawasan wisata Sigolo-golo. Pengumpulan data dilakukan dengan menggunakan metode Visual Encounter Survey (VES). Hasil penelitian yang dilakukan di tiga lokasi menunjukkan bahwa terdapat 12 spesies dari lima famili, yaitu Libellulidae, Euphaeidae, Calopterygidae, Chlorocyphidae, Platicnemididae dengan total 319 individu. Nilai kelimpahan relatif yang tinggi pada penelitian ini yaitu Pantala flavescens dengan nilai sebesar 77.40%. Nilai keanekaragaman jenis pada lokasi ini adalah H' = 0.984, yang menunjukkan bahwa nilai indeks keanekaragaman tergolong rendah.